Ketersediaan Makanan Di Sekolah Dan Kontribusinya Terhadap Rekomendasi Konsumsi Gula, Garam, Lemak - Nisrina Sabrina; Tjarono Sari; Noor Tifauzah (POLTEKKES KEMENKES YOGYAKARTA, 2019)
The age of school children has the freedom to choose foods that they like. Criteria for foods that they like usually contain lots of sugar, salt, fat, and MSG (Mono Sodium Glutamate). Apart from the consumption of school children's snacks, the sugar, salt and fat content in giving a child's lunch should also not be ignored. Less or excessive consumption of sugar, salt, and fat is not good for the body, so consumption of foods high in sugar, salt, and fat that need to be controlled.Analyzing the contribution of food in schools and its contribution to the contribution of consumption of sugar, salt, and fat.This type of research is an observational study with a cross-sectional research design. The research was conducted in January 2019. The study population was all students at SD Muhammadiyah Kauman Yogyakarta with a sample of 52 students.Communicate food from lunch and snacks. The average contribution of lunch intake for sugar is 3.47% (± 0.92), salt is 30.35% (± 5.44), and fat is 18.67% (± 3.07). While the average contribution of snacks for sugar is 15.25% (± 7.54), salt is 24.66% (± 13.53), and fat is 12.23% (± 5.05).Food intake while in school have contribute to the intake of sugar, salt, and fat.